ANALISIS PENGUKURAN KUALITAS LAYANAN PADA JARINGAN 4G - I P Indra Ully Widhi Nugraha; N Gunantara; IGAK Diafari Djuni Hartawan (Jurnal SPEKTRUM, 2021)
The development of the North Denpasar area, especially the kelurahan and the Peguyanganvillage, has caused many migrants to come and live in the Peguyangan area and have animpact on the development of the population to increase. The population growth of the NorthDenpasar peguyangan region from year to year is growing very rapidly. The analysis methodused in the study "Measuring Service Quality on 4G Networks" with Android-based Drive Testand Application is to analyze the measurement results with standardization or Key PerformanceIndicators (KPI) which are sourced from books, articles, and journals in the field using themeasurement method using G-net Track Pro application to perform Drive Test and measureRSRP, RSRQ, SINR. Meanwhile, the Nperf application is used to measure Download, Upload,and Latency. Based on the results of the measurement of the signal strength in the PeguyanganKelurahan, North Denpasar, it can be concluded, From the experiments conducted from theRSRP, RSRQ, SINR data taken in the morning and evening, in the morning the results obtainedare better than in the afternoon. . The possibility of this is caused by the EU in the morning lessthan in the afternoon. From the experiments conducted from the Download, Upload, SINR datataken in the morning and evening, in the morning the results obtained are better than in theafternoon.